Respuesta :
Answer:
x = -1/3 or 0
Step-by-step explanation:
Given equation:
- [tex]36x^{2} + 12x = 0[/tex]
We can factor 12x on the L.H.S since 12x is divisible by 36x² and 12x.
[tex]\implies 36x^{2} + 12x = 0[/tex]
[tex]\implies 12x(3x + 1) = 0[/tex]
This can lead to two solutions. I have listed them below!
Solution 1:
Divide 12x on both sides to open the parentheses.
[tex]\implies 12x(3x + 1) = 0[/tex]
[tex]\implies \dfrac{12x(3x + 1)}{12} = \dfrac{0}{12}[/tex]
Note: zero divided by any non-zero number is 0.
[tex]\implies \dfrac{12x(3x + 1)}{12} = \dfrac{0}{12}[/tex]
[tex]\implies 3x + 1 = 0[/tex]
Isolate 3x on one side of the equation.
[tex]\implies 3x + 1 = 0[/tex]
[tex]\implies 3x = 0 - 1[/tex]
[tex]\implies 3x = -1[/tex]
Divide 3 both sides to determine the value of x.
[tex]\implies 3x = -1[/tex]
[tex]\implies \dfrac{3x}{3} = \dfrac{-1}{3}[/tex]
[tex]\implies \boxed{x = \dfrac{-1}{3}}[/tex]
Solution 2:
Divide (3x + 1) on both sides to isolate 12x.
[tex]\implies 12x(3x + 1) = 0[/tex]
[tex]\implies \dfrac{12x(3x + 1)}{(3x + 1)} = \dfrac{0}{(3x + 1)}[/tex]
Note: zero divided by any non-zero number is 0.
[tex]\implies \dfrac{12x(3x + 1)}{(3x + 1)} = \dfrac{0}{(3x + 1)}[/tex]
[tex]\implies 12x = 0[/tex]
Divide 12 both sides to determine the value of x.
[tex]\implies 12x = 0[/tex]
[tex]\implies \dfrac{12x}{12} = \dfrac{0}{12}[/tex]
[tex]\implies \boxed{x = 0}[/tex]
Therefore, the solutions for x are -1/3 or 0.
Learn more about this topic: https://brainly.com/question/295675
Answer:
x = 0 or x = -1/3
Step-by-step explanation:
In the equation 36x²+12x=0 we have :
36x² = 6x × (6x)
12x = 2 × (6x)
This means that 6x is a common factor,so let’s factor :
36x²+12x=0
⇔ 6x × (6x) + 2 × (6x) = 0
⇔ 6x × (6x + 2) = 0
⇔ 6x = 0 or 6x + 2 = 0
⇔ x = 0 or x = -2/6